Portrait of Women in Palito Ni Si Boru Toba Novel - Gultom, Eva Solina (Huele: Journal of Applied Linguistics, Literature and Culture, 2025)
This paper explores the portrayal of women in the novel "Palito Ni Si Boru Toba," highlighting the dynamics and struggles faced by women in Batak society under patriarchal norms. This topic is crucial to understand the broader implications of gender roles, social justice, and identity within cultural contexts. The analysis employs a thematic approach, focusing on character analysis and the representation of women's experiences. By examining the character of Si Boru Toba, the study reveals how women navigate societal pressures, asserting their rights and identities amidst marginalization. The findings illustrate the resilience of women who strive to balance family responsibilities with personal aspirations, emphasizing the importance of solidarity in overcoming challenges. This paper not only celebrates women's courage but also invites readers to reflect on the ongoing quest for justice and equality in contemporary society.